A new algorithm for synthesising locally most consistent priorities in analytic hierarchy process for group decision making. (3rd April 2020) - Srdjevic, Bojan; Srdjevic, Zorica; Blagojevic, Bosko
The analytic hierarchy process (AHP) is an efficient tool in supporting group decision making processes because it is offering various possibilities to aggregate individual opinions, judgments and/or priorities into group equivalents, allowing control over the consistency of participating individuals. This paper proposes a straightforward procedure to locally identify: 1) the most consistent decision maker; 2) an associated prioritisation method; 3) the corresponding best local priority vector (set of weights in given node of hierarchy), to be used for the final AHP synthesis. Minimum total Euclidean distance as a universal consistency measure for the hierarchy is guaranteed on the group of decision makers and on a set of most used matrix and optimisation prioritisation methods. The algorithm is named as AHP-DPE and is applicable to any complete hierarchy (which is a philosophical pillar of AHP), for any size of a group and for any number of prioritisation methods. Selected example from agriculture illustrates how proposed methodology can be efficiently applied to obtain trustful solution in the group decision making context.